Takayasu Arteritis Initially Mimicking Infective Endocarditis - Aytekin Alcelik; Sevim Karacay; Ismail Necati Hakyemez; Busra Akin; Serkan Ozturk; Haluk Savli (Mediterranean Journal of Hematology and Infectious Diseases)
Takayasu’s arteritis (TA) is a chronic inflammatory disease that affects large vessels, predominantly the aorta and main branches, leading to vessel wall thickening, fibrosis and stenosis. Cardiac and vascular symptoms are also commonly present at disease onset. In TA with thoracic or abdominal involvement, although murmur can be present as a physical examination finding, the pulse difference may be absent. Here, we mention a case of TA who initially looked like infective endocarditis and had widespread thoracic murmur.